The hospitality industry in Sub-Saharan Africa - Ramawela, Mmatšatši (Henry Stewart Talks, 2024)
African tourism, Accommodation, Food service, Hotel industry, Next gen hospitality, Workspaces, Infrastructure development, Ubuntu